President’s Message - Mushayandebvu, Barbara (Operating Room Nurses Association of Canada Journal, 2018)
By the time you are reading this another Perioperative Nurses Week (PNW) will have come and gone. I hope everyone had the opportunity to celebrate each other and the incredible work we do every day. I look forward to seeing the entries, for the ORNAC contest, showing what this year’s PNW theme, Perioperative Nursing: Advocacy for Our Patients Through Best Practice Initiatives, means to you. And please share with on ORNAC social media, and with your work colleagues, all the fun and educational things you did to celebrate this week.